Guyana - Carpenter, Allan, 1917-2003.; Balow, Tom (Chicago: Childrens Press, 1970)
An introduction to the geography, people, history, resources, and attractions of the small South American country which gained independence from Britain in 1966.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
NLJCols20082021
Keywords: Guyana -- Juvenile literature; Guyana; Guyana; Juvenile works